Attentional modulation of reward processing in the human brain. Issue 7 (5th December 2013) - Rothkirch, Marcus; Schmack, Katharina; Deserno, Lorenz; Darmohray, Dana; Sterzer, Philipp
Abstract Although neural signals of reward anticipation have been studied extensively, the functional relationship between reward and attention has remained unclear: Neural signals implicated in reward processing could either reflect attentional biases towards motivationally salient stimuli, or proceed independently of attentional processes. Here, we sought to disentangle reward and attention‐related neural processes by independently modulating reward value and attentional task demands in a functional magnetic resonance imaging study in healthy human participants. During presentation of a visual reward cue that indicated whether monetary reward could be obtained in a subsequent reaction time task, participants either attended to the reward cue or performed an unrelated attention‐demanding task at two different levels of difficulty. In ventral striatum and ventral tegmental area, neural responses were modulated by reward anticipation irrespective of attentional demands, thus indicating attention‐independent processing of reward cues. By contrast, additive effects of reward and attention were observed in visual cortex. Critically, reward‐related activations in right anterior insula strongly depended on attention to the reward cue. Dynamic causal modelling revealed that the attentional modulation of reward processing in insular cortex was mediated by enhanced effective connectivity from ventral striatum to anterior insula. Our results provide evidence for distinct functional roles of the brain regions involved in the processing of reward‐indicating information: While subcortical structures signal the motivational salience of reward cues even when attention is fully engaged elsewhere, reward‐related responses in anterior insula depend on available attentional resources, likely reflecting the conscious evaluation of sensory information with respect to motivational value. Hum Brain Mapp 35:3036–3051, 2014. © 2013 Wiley Periodicals, Inc.